Maternal history of miscarriages and measures of fertility in relation to childhood asthma. Issue 2 (4th December 2018) - Magnus, Maria Christine; Karlstad, Øystein; Parr, Christine Louise; Page, Christian M; Nafstad, Per; Magnus, Per; London, Stephanie J; Wilcox, Allen J; Nystad, Wenche; Håberg, Siri Eldevik
Abstract : Background: It remains unclear what underlies the greater risk of asthma reported among children conceived by assisted reproductive technologies (ART). Objective: Our aim was to clarify the role of parental subfertility and unmeasured confounding on the association between ART and childhood asthma, and to examine the possibility for common mechanisms underlying parental subfertility and miscarriages influencing asthma pathogenesis. Methods: We used data from national Norwegian health registries (n=474 402) and the Norwegian Mother and Child Cohort Study (MoBa) (n=75 797). We used log-linear regression to estimate overall associations, and fixed-effects logistic regression to estimate associations within siblings. Results: ART offspring had greater asthma risk, the adjusted relative risk (aRR) was 1.20 (95% CI 1.09 to 1.32) in the registry-based cohort, and 1.42 (95% CI 1.14 to 1.76) in MoBa. The sibling analysis yielded similar associations, although the CI included the null value. The elevated asthma risk among ART offspring was attenuated when they were compared with spontaneously conceived offspring with time to conception >12 months, aRR 1.22 (95% CI 0.95 to 1.57). Asthma risk also increased with maternal history of early miscarriages (≤12 weeks), with an aRR of 1.07 (95% CI 1.03 to 1.11) for one, aRR 1.18 (95% CI 1.10 to 1.26) for two and aRR 1.24 (95% CI 1.12 to 1.37) for three or more. Conclusion: Our findings indicate that both parental subfertility and characteristics related to the ART procedure itself might increase offspring asthma risk, although this needs to be confirmed in future studies, and further suggest that common mechanisms underlying parental subfertility and recurrent miscarriages might influence offspring asthma pathogenesis.